Abnormal quantitative sudomotor axon reflex test results in patients with tinnitus as a possible indicator of small fiber neuropathy - Lee, Hye Lim; Lyou, Hyun Ji; Song, Jae-Jun; Kim, Chi Kyung (Frontiers in Neurology, 2024)
A few cases of small fiber neuropathy (SFN) and tinnitus (TN) associated with coronavirus disease 2019 have been reported. However, the relationship between SFN and TN has not been studied. This study investigated a possible relationship between SFN and patients with TN (PwTNs) using autonomic function tests (AFTs) including quantitative sudomotor axon reflex tests (QSART). We performed QSARTs and other AFTs such as the Sympathetic skin response (SSR), Valsalva ratio (VR), and heart rate variability (HRV). The QSART results, obtained at seven hospitals using same protocols, were compared between PwTNs and healthy controls. We confirmed the abnormalities in SSR, VR, and HRV in PwTNs, although those parasympathetic AFTs were not performed in healthy controls. Additionally, we checked Tinnitus handicap inventory (THI) scores for PwTNs and ~50% of PwTNs had low-grade disability, whereas 9.3% had high-grade disability. Data from 57 PwTNs and 122 healthy controls were analyzed. The sweat volumes of QSART in the older age group tended to be higher in the PwTNs than in age-matched healthy controls, and significant differences between the PwTN and control groups were observed in the feet in both sexes (p < 0.001) and in the arms in women (p = 0.013). In the younger age group, the sweat volumes in the feet of men were higher in PwTNs than in healthy controls (p = 0.017). No association was observed between THI and QSART scores. In this study, the sweat volumes in QSARTs were higher in PwTNs than in healthy controls. However, abnormal SSR, HRV, and VR results were not commonly observed in PwTNs. Although the results should be interpreted with caution because of limitations in study, PwTNs might also have SFN apart from dysautonomia. This is the first study to perform QSART with other parasympathetic AFTs in PwTNs. However, larger and more rigorously controlled studies will be needed to reveal the relationship between SFN and TN in the future.